Penerapan Asas Lex Loci Contractus dan Lex Causae Terhadap Perkara IPB dan Amerika dalam Hukum Perdata Internasional - Putri, Lorena Andrea; Budimansyah, Afriyadi; Pratama, Yoga D; Own.K, Chesario; Amalya, Maulina (Indonesian Journal of Law and Justice, 2023)
Law is a unity formed to regulate everything something that happens in society. International law has 2 basic types, namely; Lex Loci Contractus Principle and Lex Loci Causae Principle. Normative writing method by searching library materials as well as reading material from sources related to the problem being studied. IPB case and America, namely regarding the delivery of 800 monkeys one of the monkeys' tail fell off and experienced postnatal stress, Finally, IPB doctors euthanized the baby monkey and paralyze the mother. Because of this incident, America filed a lawsuit against Indonesia regarding achievements in the form of reduction of 800 monkeys. Application of the Lex Loci Contractus Principle and Lex Causae is certainly effective, because it was proven during the process If the case is held, the law used meets the theory Legal Certainty, where Indonesian law is used in accordance with application of the principles in the existing agreement between IPB and America.